Co-constructing early childhood programs nourished by Inuit worldviews - Rowan, Mary (Études/Inuit/Studies, 2014)
Saimaqatigiingniq is defined as the place where Inuit and Qallunaat meet in the middle and are reconciled (Qikiqtani Inuit Association 2010). In this paper, the researcher, a middle-aged white woman with more than 30 years of experience living, visiting, and working with Inuit in the Arctic, employs a series of questions to examine the challenge of the Qikiqtani Truth Commission, which invites Inuit and Qallunaat to do things in new ways. These questions include: What is the potential of saimaqatigiingniq and in what context? How can saimaqatigiingniq facilitate the organization of early childhood programs and services that are meaningfully structured with Inuit worldviews? What is to be considered when seeking to think with Inuit perspectives in research? What are examples of Inuit approaches to child rearing? What is the rationale and what are the dimensions for reconceptualizing early childhood education from Inuit perspectives?